PRODUKSI UDANG DAN POLA MUSIM PENANGKAPANNYA DI PERAIRAN KABUPATEN PANGKEP - Ihsan ihsan; Mustamin Tajuddin (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
Shrimp is a type of crustacean and is included in the marine fishery commodity which has important economic value and is currently hunted by fishermen and is commonly found in coastal waters. The purpose of this study was to determine the Shrimp Production and Seasonal Catching Pattern in the Waters of Pangkep Regency. Its usefulness is as a foundation material in the use of shrimp resources in the waters of Pangkep Regency. Data collected consists of primary data and secondary data. Primary data is obtained by direct observation in the field through a field survey method (visual recall) to portray the conditions of crab resources. While secondary data was collected from the relevant agencies according to the attributes that will be reviewed and recorded data from collecting fishermen in the coastal areas and small islands of Pangkep Regency. Shrimp production from trammel net and mini trawl catches in the waters of the Sigeri District of Pangkep Regency in 2015 consisted of 706 tons of white shrimp and dogol shrimp 4,481 tons, while in 2016 706 tons of white shrimp and dogol shrimp 4,481 tons. Analysis of the percentage of shrimp fishing season index in the waters of Pangkep Regency, occurred in January, February, March and April. The highest percentage of fishing season index occurs in January each year.